Functional outcomes of displaced midshaft clavicle fractures treated with precontoured locking compression plates. A prospective observational study. - Dr. D. Sneha; Dr.Thatipamula Praful Kumar MBBS,DNB (Student’s Journal of Health Research Africa, 2025)
Background: Displaced midshaft clavicle fractures are common injuries in active adults. Although conservative treatment has been the traditional approach, surgical fixation using precontoured locking compression plates (LCPs) offers potential benefits of anatomical reduction, stable fixation, and early rehabilitation. This study evaluated functional outcomes, union rates, and complications following open reduction and internal fixation with precontoured LCPs. Methods: A prospective observational study was conducted on 30 patients aged >18 years with displaced midshaft clavicle fractures (Allman Group I) treated at a tertiary care center between April 2018 and September 2019. Open fractures, proximal or distal third fractures, pathological fractures, neurovascular injury, and nonunion cases were excluded. All patients underwent open reduction and internal fixation with precontoured LCPs. Functional outcomes were assessed using the Constant–Murley score at a minimum of 6 months follow-up. Radiological union was confirmed by callus formation and the absence of a fracture line. Data were analyzed descriptively. Results: The mean age was 37.4 years; males comprised 73.3% of cases (male: female ratio 2.75:1). Road traffic accidents were the predominant cause (70%), and the right clavicle was more frequently involved (60%). The mean union time was 10.33 ± 1.2 weeks, with 90% achieving full shoulder range of motion by 6 months. Constant–Murley scores showed 73.3% excellent, 20.0% good, 3.3% fair, and 3.3% poor outcomes. Good-to-excellent results were achieved in 93.3% of cases. No nonunions or implant failures occurred; minor complications were limited to transient stiffness in 10% of patients. Conclusion: Precontoured LCP fixation for displaced midshaft clavicle fractures provides high union rates, excellent functional outcomes, and minimal complications. Early mobilization and rigid fixation contribute to favorable results. Recommendations: Precontoured LCP fixation should be considered in active adults with displaced midshaft clavicle fractures to optimize recovery and reduce disability.